Selling the ‘City of Sails’: Destination Branding Through the 2021 America’s Cup - Barron, Christopher (Auckland University of Technology, 2020)
In 2021, the Royal New Zealand Yacht Squadron will become the first non-American sailing club to have hosted an America’s Cup regatta on more than two occasions. This provides those responsible for promoting Auckland and New Zealand to the rest of the world, with a somewhat unique opportunity. One pre-event impact report estimates that between $600 million and $1 billion will be injected to New Zealand's economy between 2018 and 2021. This research examines the tourism legacy planning and destination branding attached to major events hosted in Auckland over the past two decades (2000-present). It also explores the extent to which New Zealand’s largest city can leverage new and old legacies through their hosting of the 2021 America’s Cup (AC36). Using both primary and secondary data, this study critically explores the existing Mega Sport Event management and marketing discourse before examining the literature on stakeholder mapping tools to identify the key players (i.e. those with power and interest), plus those other stakeholders who require a sustained effort to ensure they are appropriately engaged and informed. To supplement primary data, Google analytics explores the past and present use of the terms ‘Auckland’ and ‘City of Sails’, using a comparative Key Word Search to identify how the phrases have been and potentially continue to be an important brand for Auckland. Three semi-structured interviews were also conducted with a cross-section of key AC36 stakeholders, allowing the researcher the opportunity to identify expectations around short-term and long-term return on investment generation for them (their employer) and the host community. Thematic analysis was employed to extract key themes and recurring features from the interview transcripts. The finding, conclusions and recommendations from this research focus upon the urban destination branding strategies that can be applied prior to the hosting of Mega Sport Events and/or the hosting of unique major sports events such as the 2021 America’s Cup. Finding from this research reinforces the notion that Mega Sport Events can be leveraged for destination branding and to develop socio-economic and tourism legacies. This study identifies that through Auckland’s hosting of the 2021 Americas cup there is an opportunity to reinforce the city’s position as a world-class tourist destination and develop socio-economic legacies that grow the economy and reflect Auckland’s unique cultural heritage.
Keywords: Sport Management; Major Sport Event Management; Sport Marketing; Destination Branding; America's Cup; Leveraging of legacies